An Ad Hoc Nation: An Analysis of Moldovan Election Campaign Clips. (November 2015) - Danero Iglesias, Julien
Since independence, nationalism has been at the front of politics in the Republic of Moldova in the context of a persisting political struggle about the very definition of the Moldovan nation. Looking at campaign video clips produced in 2009 by Moldovan political parties and using a methodology inspired by Critical Discourse Analysis, the article gives a better understanding of nationalism in Moldova nowadays. The article demonstrates that the focus of political parties on the nation is purely symbolic. They adapt their discourse to the context in which they evolve (audience of the videos and targeted voters). Pursuing the objective of gaining or holding on to power, parties construct an ad hoc nation whose content they fill with the needs of the moment, using mirroring arguments to win the elections over competing parties seen as enemies of an endangered country.